Futuristic cemetery designs, visions of the future funerary architecture - Ing. arch. Mária Jurášková, PhD. (Slovak University of Technology, Faculty of Architecture and Design, 2020)
Several important trends influence modern metropolises, including globalization, multiculturalism and overpopulation resulting in lack of free space. These trends relate to funerary culture in a specific way. As traditional cemeteries require sizeable ground space, graveyard plots are becoming less and less available in big cities. Cremations are on the rise, but even funerary urns need places to rest which are more and more difficult to find. Futuristic cemetery design, visions of funerary architecture of the future, are trying to answer these challenges by seeking innovative solutions. In our article, we present several concepts of futuristic cemeteries which represent various types of innovative approaches. They are: vertical cemeteries, underground cemeteries, cemeteries floating on water and green cemeteries. We briefly describe the advantages and disadvantages of each type and continue with more detailed descriptions, using one concept per each of the aforementioned types: "The Last House" for vertical cemeteries, "Metro Pére Lachaise" for underground cemeteries, "Columbarium at Sea" for cemeteries floating on water, and "Moksha Tower" for green cemeteries. These concepts show that taking a new perspective on funerary architecture can bring interesting solutions. The question remains as to what the society will be willing to accept. This will be the determining factor whether the presented concepts will remain blueprints forever or become a reality one day.